2005
DOI: 10.1152/jn.01002.2003
|View full text |Cite
|
Sign up to set email alerts
|

Can Delay-Period Activity Explain Working Memory?

Abstract: Working-memory tasks often lead to elevated delay-period discharge rates in cortical neurons. When this altered neuronal discharge rate, called delay activity, shows stimulus specificity, it is a good candidate for a neuronal mechanism of working memory. If the delay activity is indeed the carrier of memory, then experimental manipulation during the delay period that disrupts delay activity should also disrupt behavioral performance. We tested this hypothesis in two macaque monkeys with a delayed matching-to-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Sound frequency information (i.e., pitch) is parametrically maintained by the firing rates of primate PFC neurons during the delay period (e.g., high pitch stimuli produce high spike rates-e.g., Brody et al, 2003;Romo et al, 1999). Evoked or spontaneous disruptions of these sustained activities are correlated with the failure of maintenance (e.g., Fuster, 1973;Quintana et al, 1988;Sobotka et al, 2005;Wang et al, 2011), supporting the importance of sustained neural activity during the delay periods for the maintenance of information in working memory.…”
Section: Electrophysiological Studiesmentioning
confidence: 87%
“…Sound frequency information (i.e., pitch) is parametrically maintained by the firing rates of primate PFC neurons during the delay period (e.g., high pitch stimuli produce high spike rates-e.g., Brody et al, 2003;Romo et al, 1999). Evoked or spontaneous disruptions of these sustained activities are correlated with the failure of maintenance (e.g., Fuster, 1973;Quintana et al, 1988;Sobotka et al, 2005;Wang et al, 2011), supporting the importance of sustained neural activity during the delay periods for the maintenance of information in working memory.…”
Section: Electrophysiological Studiesmentioning
confidence: 87%
“…In addition to long-term memory, working memory within temporal cortex has been the subject of monkey studies (Baylis and Rolls 1987;Davachi and Goldman-Rakic 2001;Eskandar et al 1992;Fuster 1990;Fuster and Jervey 1981;Holscher and Rolls 2002;Miller and Desimone 1994;Miller et al 1991;Miyashita and Chang 1988;Nakamura and Kubota 1995;Sobotka et al 2005). Working memory is believed to be closely related to attention (Awh and Jonides 2001;Awh et al 2006;Barnes et al 2001;de Fockert et al 2001;Desimone 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the effect of SOA between hippocampal ES and the presentation of retrieval cues, using the present three-phase dual-task paradigm, could reveal much about the dynamic interdependence of encoding and retrieval activities within the hippocampus. Sobotka et al (2005) also showed recently that delay-interval ES directly in the monkey hippocampus, persisting for 125-250 ms but delivered 1 s after onset of the sample stimulus, disrupts recognition in a short-term delayed matching-to-sample task. Their findings, in conjunction with our own and those of Coleshill et al (2004), suggest that the hippocampus may be differentially engaged, or controlled, in long-term versus short-term (working) memory tasks.…”
Section: Discussionmentioning
confidence: 80%